Simultaneous temperature and humidity measurements in a mechanical ventilator using an optical fibre sensor - Hernandez, F.U.; Correia, R.; Morgan, S.P.; Hayes-Gill, B.; Evans, D.; Sinha, R.; Norris, A.; Harvey, D.; Hardman, J.G.; Korposh, Sergiy (2016)
An optical fibre sensor for simultaneous temperature and humidity measurements consisting of one fibre Bragg grating (FBG) to measure temperature and a mesoporous film of bilayers of Poly(allylamine hydrochloride)(PAH) and silica (SiO2) nanoparticles deposited onto the tip of the same fibre to measure humidity is reported. The hygroscopic film was created using the layer-by-layer (LbL) method and the optical reflection spectra were measured up to a maximum of 23 bilayers. The temperature sensitivity of the FBG was 10 pm/°C while the sensitivity to humidity was (-1.4x10-12 W / %RH) using 23 bilayers. The developed sensor was tested in the mechanical ventilator and temperature and humidity of the delivered artificial air was simultaneously measured. Once calibrated, the optical fibre sensor has the potential to control the absolute humidity as an essential part of critical respiratory care. © (2016) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.